Peningkatan Peran Jenis Kelamin Melalui Bermain Peran - Suryana, Nana (Al-aqidah | Jurnal Studi Islam, 2019)
This research is a classroom action research by using model Kemmis and Mc. Taggart. The aim of research was describle to implemetate of playing processing at TK B Azahra Kabayoran Baru South Jakarta, supports of 15 children, namely: 7 women and 8 men. Steps: (1) planning; (2) implementation; (3) observation; (4) reflection. Analysis of the data used is qualitative and quantitative. The qualitative data uses the Miles and Hubberman models, in two cycles, namely cycle I and cycle II. The final results of data analysis show an increase from cycle II. The quantitative results of the pre-cycle reached an average score of 9.73 %, that is, the category had not developed, the first cycle had an average of 32.02 % in the very well-developed category, in the second cycle had an average cycle of 35.02 % in the very well developed category